Electrochemical device and electronic apparatus

By setting a soluble polymer cladding layer on the surface of silicon particles, the problem of rebound in silicon material thickness in lithium-ion batteries is solved, and the circulation and rate performance of the battery is improved, especially under high temperature conditions.

CN119213581AActive Publication Date: 2024-12-27NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202380037316.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2024-12-27
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

Silicon materials have thickness rebound problems during the processing of lithium-ion batteries, resulting in poor circulation and rate performance.

Method used

The soluble polymer coating layer is provided on the surface of the silicon particles. After the coating layer is dissolved in the electrolyte, a large gap is formed between the silicon particles and the surrounding particles, reducing the extrusion effect of the expansion on the surrounding particles, thereby improving the electrode sheet Thickness expansion rate and cycling performance.

Benefits of technology

By improving the thickness expansion rate of the electrode sheet, the circulation and rate performance of lithium-ion batteries are improved, especially under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BSB0000209735060000111
    Figure BSB0000209735060000111
  • Figure BSB0000209735060000121
    Figure BSB0000209735060000121
  • Figure BSB0000209735060000141
    Figure BSB0000209735060000141
Patent Text Reader

Abstract

Disclosed are a negative pole piece, an electrochemical device and an electronic equipment, the electrochemical device comprising a negative pole piece, the negative pole piece comprising a negative active material, the negative active material comprising a silicon-based material, the silicon-based material being obtained by arranging a surface coating layer on the surface of a silicon particle, the surface coating layer comprises a soluble polymer, the soluble polymer is soluble in an electrolyte, and after the electrochemical device is injected into the electrolyte, the mass concentration of the soluble polymer in the electrolyte is 0.2 wt% to 6 wt%. The soluble polymer is soluble in the electrolyte, and gaps are reserved between silicon particles and surrounding particles after dissolution, so that the thickness swelling rate of the pole piece is improved, and the cycle performance and the rate capability of the lithium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrochemical device and an electronic device. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high operating voltage, and low environmental pollution. They have been widely used in various small portable devices such as mobile phones, digital cameras, laptops, and drones. Among non-carbon negative electrode active materials, the theoretical gram capacity of silicon materials can reach 4200mAh / g, which is 10 times higher than the currently commercialized graphite negative electrode. The use of silicon negative electrodes can greatly improve the energy density of lithium-ion batteries. However, the relatively low compaction density of silicon materials causes a very significant rebound in the thickness of silicon pole pieces during processing, resulting in unsatisfactory cycle performance and rate performance of lithium-ion batteries containing silicon negative electrodes. Summary of the invention

[0003] In view of this, the present application provides an electrochemical device and an electronic device. The electrochemical device described in the present application provides a surface coating layer on the surface of silicon particles. After the silicon particles containing the surface coating layer come into contact with an electrolyte, the surface coating layer will dissolve, so that the silicon particles have a larger expansion space, thereby improving the problem of thickness rebound of silicon system electrodes during processing.

[0004] In the first aspect, the present application provides a negative electrode plate. The negative electrode plate includes a negative electrode active material. The negative electrode active material includes a silicon-based material, and the silicon-based material is obtained by setting a surface coating layer on the surface of silicon particles, and the surface coating layer includes a soluble polymer, and the soluble polymer is configured to be soluble in the electrolyte. After the surface coating layer is dissolved, there is a large gap between the silicon particles and the surrounding particles. During the charge and discharge process, the expansion of the silicon particles has a small squeezing effect on the surrounding particles, so the overall expansion of the pole piece is greatly improved, thereby improving the expansion problem during the cycle and improving the rate performance of the battery.

[0005] In some embodiments, after the electrochemical device is injected with an electrolyte, the soluble polymer will dissolve in the electrolyte. The mass ratio of the soluble polymer to the silicon particles is 0.05 to 1.2:1. When the mass ratio of the soluble polymer to the silicon particles meets the above range, it is beneficial to improve the thickness expansion rate of the pole piece and improve the cycle performance of the lithium-ion battery.

[0006] In some embodiments, further, the mass ratio of the soluble polymer to the silicon particles is 0.3 to 0.5: 1. When the mass ratio of the soluble polymer to the silicon particles meets the above range, it is beneficial to further improve the thickness expansion rate of the pole piece and improve the cycle performance of the lithium-ion battery.

[0007] In some embodiments, the surface coating layer further comprises carbon nanotubes; the mass ratio of the carbon nanotubes to the silicon particles is 0.005 to 0.1: 1. When the mass ratio of the carbon nanotubes to the silicon particles is within the above range, it is beneficial to further improve the thickness expansion rate of the pole piece and improve the cycle performance of the lithium-ion battery.

[0008] In the second aspect, the present application provides an electrochemical device, which includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode active material, wherein the negative electrode active material includes a silicon-based material, wherein the silicon-based material is obtained by providing a surface coating layer on the surface of silicon particles, wherein the surface coating layer includes a soluble polymer, wherein the soluble polymer is soluble in the electrolyte, and wherein the silicon particles after the surface coating layer is dissolved have a large gap with the surrounding particles, and during the charge and discharge process, the expansion of the silicon particles has a smaller squeezing effect on the surrounding particles, thereby greatly improving the overall expansion of the electrode plate, thereby improving the expansion problem during the cycle and enhancing the rate performance of the battery.

[0009] In some embodiments, after the electrochemical device is injected into the electrolyte, the soluble polymer will dissolve in the electrolyte, and further, the mass concentration of the soluble polymer in the electrolyte is 0.2wt% to 6wt%. The mass concentration of the soluble polymer in the electrolyte is within the above range, which is conducive to improving the thickness expansion rate of the pole piece and improving the high temperature cycle performance of the lithium ion battery. Preferably, the mass concentration of the soluble polymer in the electrolyte is 1.3wt% to 1.5wt%.

[0010] In some embodiments, the electrolyte includes a linear ester and a cyclic ester, and the mass ratio of the linear ester to the cyclic ester is (1-4):(4-1). At this time, the ionic conductivity of the electrolyte is suitable, which is conducive to dissolving the soluble polymer in the surface coating layer on the one hand, and can be better freed in the pores of the negative electrode plate on the other hand, which is conducive to improving the rate performance of the lithium ion battery. Preferably, the mass ratio of the linear ester to the cyclic ester is (1-3):1.

[0011] In some embodiments, the soluble polymer comprises an alcohol-soluble resin, and the alcohol-soluble resin is selected from at least one of an alcohol-soluble polyamide resin, an alcohol-soluble acrylic resin, or an alcohol-soluble polyurethane resin. Preferably, the alcohol-soluble resin comprises an alcohol-soluble polyurethane resin.

[0012] In some embodiments, the molecular weight of the alcohol-soluble resin is 8*10 3 Up to 1.5*10 5The molecular weight of the alcohol-soluble resin is within the above range, which is more conducive to achieving an appropriate mass concentration of the alcohol-soluble resin in the electrolyte, so that the surface of the silicon particles has a larger free expansion space, which is more conducive to reducing the thickness expansion rate of the electrode.

[0013] In some embodiments, the mass ratio of the soluble polymer to the silicon particles is 0.05 to 1.2: 1. Preferably, the mass ratio of the soluble polymer to the silicon particles is 0.3 to 0.5: 1. In this case, it is more conducive to improving the thickness expansion rate of the negative electrode sheet.

[0014] In some embodiments, the mass ratio of the carbon nanotubes to the silicon particles is 0.005:1 to 0.1:1. Preferably, the mass ratio of the carbon nanotubes to the silicon particles is 0.01 to 0.05:1.

[0015] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes, and the aspect ratio of the single-walled carbon nanotubes is 1*10 4 Up to 4*10 4 Preferably, the aspect ratio of the single-walled carbon nanotube is 2.5*10 4 Up to 3*10 4 .

[0016] In some embodiments, the dissolution amount of the soluble polymer in a specific solution is >80%, and the specific solution includes a linear ester and a cyclic ester, and the mass ratio of the linear ester to the cyclic ester is 3: 1. The dissolution amount refers to the mass of the soluble polymer dissolved in the solution after being immersed in the specific solution at 60°C.

[0017] The test method for the dissolution amount includes: preparing a film with the soluble polymer and weighing m0, soaking the film prepared by the polymer in the specific electrolyte at 60°C until the weight of the film no longer changes; taking out the soaked film and weighing it after drying it, which is calculated as the mass m1; the dissolution amount C0 = (m0-m1) / m0.

[0018] In some embodiments, the porosity of the negative electrode sheet is 25% to 48%. Preferably, the porosity of the negative electrode sheet is 25% to 33%.

[0019] In some embodiments, the contact angle of the negative electrode plate to the electrolyte is 0° to 45°.

[0020] In some embodiments, the negative electrode active material further contains graphite, and the mass ratio of the silicon particles to the graphite is 1:23 to 29:1.

[0021] In some embodiments, the thickness of the surface coating layer is 0.5 μm to 10 μm. Preferably, the thickness of the surface coating layer is 2 μm to 3 μm.

[0022] It should be noted that the thickness of the surface coating layer changes accordingly with the change in the mass ratio m1 / m2 of the soluble polymer to the silicon particles. Specifically, m1 is the mass fraction of the soluble polymer, and m2 is the mass fraction of the silicon particles. When the mass fraction m1 of the soluble polymer is reduced (that is, the mass ratio decreases), the thickness of the surface coating layer also decreases. When the mass fraction m1 of the soluble polymer is increased (that is, the mass ratio increases), the thickness of the surface coating layer also increases.

[0023] In a third aspect, the present application provides an electronic device, which includes the above-mentioned electrochemical device.

[0024] The beneficial effects brought by the technical solutions provided in some embodiments of the present application include at least: the present application provides an electrochemical device, in which the surface of the negative electrode active material silicon particles is coated with a surface coating layer, the surface coating layer contains a soluble polymer, the soluble polymer is soluble in the electrolyte, and after dissolution, a gap is reserved between the silicon particles and the surrounding particles. At this time, on the one hand, during the charge and discharge process, the expansion of the silicon particles has a small squeezing effect on the surrounding particles, which is conducive to improving the thickness expansion rate of the pole piece, thereby improving the cycle performance of the lithium-ion battery, especially the high-temperature cycle performance. On the other hand, it is conducive to the electrolyte being better freed in the pores of the negative electrode plate, thereby improving the rate performance of the lithium-ion battery. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0026] At present, the improvement of low compaction density of high-capacity silicon-based materials is mainly concentrated in the following aspects: 1) Improving particle size or morphology, such as nano-sizing of SiO and SiC. Nanomaterials can alleviate the volume effect to a certain extent, and have better stacking effect and better compaction density; 2) Using new adhesives with high adhesion. However, there are two common problems with the use of composite nanocomposite materials such as SiO and SiC. The gram capacity of Si composite materials is lower than that of pure Si, and the actual reversible gram capacity is lower. For example, the gram capacity of SiO negative electrode materials is 2400mAh / g, and the actual reversible gram capacity is about 1500mAh / g; another common problem of silicon composite materials is that the electrode is pulverized during the cycle, resulting in failure of the electronic and ion conductive paths and poor cycle performance; and due to the complex process of composite materials, the preparation cost of nanostructured Si materials is still very high. While reducing the size of Si from bulk to nanoscale, the processing cost will at least double.

[0027] In order to solve the thickness rebound of silicon materials during the processing, which leads to a series of problems such as the inability to maximize the energy density of the silicon system and poor cycle performance, the present application provides a negative electrode plate and an electrochemical device including the negative electrode plate, which can solve the thickness rebound of the silicon system plate during the processing.

[0028] Electrochemical Devices

[0029] The electrochemical device comprises a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte.

[0030] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material. The silicon-based material is obtained by arranging a surface coating layer on the surface of silicon particles. The surface coating layer includes a soluble polymer, and the soluble polymer is soluble in an electrolyte. After the electrochemical device is injected into the electrolyte, the mass concentration of the soluble polymer in the electrolyte is 0.2wt% to 6wt%.

[0031] Exemplarily, after the electrochemical device is injected into the electrolyte, the mass concentration of the soluble polymer in the electrolyte is 0.2wt%, 0.5wt%, 0.8wt%, 1wt%, 1.3wt%, 1.5wt%, 1.8wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 6wt% or a range consisting of any two of the above values.

[0032] In some embodiments, the soluble polymer includes an alcohol-soluble resin, and the alcohol-soluble resin is selected from at least one of an alcohol-soluble polyamide resin, an alcohol-soluble acrylic resin, or an alcohol-soluble polyurethane resin.

[0033] Specifically, in some examples, the alcohol-soluble resin includes any one of an alcohol-soluble polyamide resin, an alcohol-soluble acrylic resin, and an alcohol-soluble polyurethane resin; in other examples, the alcohol-soluble resin is selected from at least two of an alcohol-soluble polyamide resin, an alcohol-soluble acrylic resin, or an alcohol-soluble polyurethane resin; in other examples, the alcohol-soluble resin includes an alcohol-soluble polyamide resin, an alcohol-soluble acrylic resin, and an alcohol-soluble polyurethane resin.

[0034] In some embodiments, the molecular weight of the alcohol-soluble resin is 8*10 3 Up to 1.5*10 5 For example, the molecular weight of the alcohol-soluble resin is 8*10 3 ,9*10 3 , 1*104 , 3*10 4 , 5*10 4 ,8*10 4 , 1*10 5 , 1.5*10 5 Or a range consisting of any two of the above values.

[0035] In some embodiments, the mass ratio of the soluble polymer to the silicon particles is 0.05 to 1.2: 1. For example, the mass ratio of the soluble polymer to the silicon particles is 0.05: 1, 0.08: 1, 0.1: 1, 0.3: 1, 0.35: 1, 0.4: 1, 0.5: 1, 0.8: 1, 1: 1, 1.2: 1, or a range consisting of any two of the above values.

[0036] In some embodiments, the mass ratio of the carbon nanotubes to the silicon particles is 0.005 to 0.1: 1. For example, the mass ratio of the carbon nanotubes to the silicon particles is 0.005: 1, 0.008: 1, 0.01: 1, 0.02: 1, 0.03: 1, 0.05: 1, 0.08: 1, 0.1: 1, or a range consisting of any two of the above values.

[0037] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes, and the aspect ratio of the single-walled carbon nanotubes is 1*10 4 Up to 4*10 4 For example, the aspect ratio of the single-walled carbon nanotube is 1*10 4 , 1.5*10 4 , 2*10 4 , 2.5*10 4 , 3*10 4 ,3.5*10 4 , 4*10 4 Or a range consisting of any two of the above values.

[0038] In some embodiments, the porosity of the negative electrode sheet is 25% to 48%. Exemplarily, the porosity of the negative electrode sheet is 25%, 28%, 30%, 33%, 35%, 38%, 40%, 45%, 48%, or a range consisting of any two of the above values.

[0039] In some embodiments, the thickness of the surface coating layer is 0.5 μm to 10 μm. For example, the thickness of the surface coating layer is 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 9 μm, 10 μm, or a range consisting of any two of the above values.

[0040] In some embodiments, the negative electrode active material layer further includes a binder. Exemplarily, the binder includes one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin, or carboxymethyl cellulose (CMC).

[0041] The negative electrode current collector may be made of metal foil or porous metal plate, for example, foil or porous plate made of metal such as copper, nickel, titanium or iron or alloys thereof, such as copper foil.

[0042] The negative electrode sheet can be prepared according to conventional methods in the art. For example, the negative electrode active material and the optional conductive agent and binder are dispersed in a solvent, and the solvent can be at least one of water, ethanol, acetone, butanone, dimethylformamide, N-methylpyrrolidone, diethylformamide, dimethyl sulfoxide or tetrahydrofuran to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the negative electrode collector, and the negative electrode sheet is obtained through drying, cold pressing and other processes. For example, the oven temperature is set to 60°C to 110°C, and the current collector coated with the slurry is dried in an oven to obtain an electrode material coating with excellent adhesion and a smooth surface, and then the other side of the current collector is coated in the same way.

[0043] Preparation method of silicon-based material

[0044] Exemplarily: carbon nanotubes and silicon particles are mixed in a mass ratio of 0.005 to 0.1:1, dispersed with a disperser at 300rpm / min to 500rpm / min for 10 to 20 minutes, then a soluble polymer is added, the mass ratio of the soluble polymer to the silicon particles is 0.05 to 1.2:1, and water is added to mix, the solid content of the mixed solution after mixing is 50% to 60%, and then dispersed with a disperser at 800rpm / min to 100rpm / min for 2 to 3 hours, and then water is added to dilute the solid content of the mixed solution to 10% to 20%, and then dispersed with a disperser at 800rpm / min to 100rpm / min for 2 to 3 hours, and the mixed solution is added to a cyclone separation tower, the temperature of the cyclone separation tower is set to 115 to 125°C, and the solid powder is collected.

[0045] The electrolyte includes an organic solvent, an electrolyte lithium salt and an additive. The organic solvent includes at least two of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) or diethyl sulfone (ESE).

[0046] In some embodiments, in the organic solvent, the mass ratio of linear ester to cyclic ester is (1-4):(4-1).

[0047] The electrolyte lithium salt includes one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate)) or LiTFOP (lithium tetrafluorooxalatophosphate).

[0048] The additives include one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), succinonitrile (SN), adiponitrile (AND), 1,3-propylene sultone (PST), tris(trimethylsilyl) phosphate (TMSP) or tris(trimethylsilyl) borate (TMSB).

[0049] other

[0050] The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector. The positive electrode active material in the positive electrode active material layer can be selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate and the above compounds plus other transition metals or non-transition metals.

[0051] For example, the positive electrode current collector may be made of a metal foil or a porous metal plate, for example, a foil or a porous plate made of a metal such as aluminum, copper, nickel, titanium or iron, or an alloy thereof, such as Al (aluminum) foil.

[0052] The positive electrode sheet can be prepared according to conventional methods in the art.

[0053] There is no particular limitation on the isolation membrane, and any known porous structure isolation membrane with electrochemical stability and chemical stability can be selected, such as single-layer or multi-layer films of one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride (PVDF).

[0054] The electrochemical device can be prepared according to conventional methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in order, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain an electrode assembly, or the electrode assembly can be obtained by winding; the electrode assembly is placed in a packaging shell, and the electrolyte is injected and sealed to obtain the electrochemical device.

[0055] The electrochemical device of the present application may include any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries or secondary batteries. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0056] Electronic devices

[0057] The electronic device of the present application includes any one of the above-mentioned electrochemical devices of the present application. The electronic device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0058] The following examples and comparative examples are given to more specifically illustrate the embodiments of the present application. Unless otherwise stated, the parts, percentages and ratios listed below are all based on weight, and the raw materials used are commercially available or synthesized according to conventional methods.

[0059] Example 1-1

[0060] Preparation of silicon-based materials

[0061] Carbon nanotubes and silicon particles were mixed at a mass ratio of 0.01:1, dispersed at 300 rpm / min for 10 min, and then polyamide resin (molecular weight 8*103 ~1.5*10 5 ), the mass ratio of the polyamide resin and the silicon particles is 0.35:1, and water is added to mix, the solid content of the mixed solution after mixing is 50%, and then dispersed with a disperser at 800rpm / min for 2h, and then water is added to dilute the solid content of the mixed solution to 10%, and then dispersed with a disperser at 800rpm / min for 2h, and then the mixed solution is added to a cyclone separation tower through a peristaltic pump, the temperature of the cyclone separation tower is set to 120°C, and the solid powder is collected to obtain.

[0062] Example 1-2 to Example 1-17

[0063] Different from Example 1-1, some parameters and parameter values ​​were adjusted during the preparation of the silicon-based material, as shown in Table 1, and the rest are the same.

[0064] Comparative Example 1

[0065] Different from Example 1-1, the silicon-based material, i.e. silicon particles with a silicon content of 10%, is not coated with a coating layer on its surface.

[0066] Comparative Examples 2 to 5

[0067] Different from Example 1-1, some parameters and parameter values ​​were adjusted during the preparation of the silicon-based material, as shown in Table 1, and the rest are the same.

[0068] Preparation of negative electrode

[0069] The prepared silicon-based material, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium methyl cellulose (CMC) were mixed evenly in a deionized water solvent at a mass ratio of 95:2:2:1, coated on one side of a 9 μm Cu foil and dried, and the above steps were repeated on the other side of the Cu foil to obtain a negative electrode sheet coated with a negative electrode active layer on both sides. The coated negative electrode sheet was dried and cold pressed, and then cut into sheets with a specification of 74 mm×800 mm for standby use.

[0070] Preparation of positive electrode

[0071] The positive electrode active material - lithium cobalt oxide active material LiCoO2, conductive carbon black Super-P, and binder PVDF are mixed in an N-methylpyrrolidone NMP solvent system at a weight ratio of 97.6:1.3:1.1 by a vacuum mixer to obtain a positive electrode slurry; the positive electrode slurry is coated on both surfaces of a 9μm Al foil substrate with a coating weight of 280mg. The coated positive electrode sheet is dried and cold pressed, and then cut into sheets with a specification of 74mm×800mm for standby use.

[0072] Preparation of electrolyte

[0073] In a glove box filled with a dry argon atmosphere, organic solvents ethylene carbonate (EC), diethyl carbonate (DEC), propyl propionate (PP) and adiponitrile (ADN) were mixed in a mass ratio of 1:2:1:0.15, and then lithium hexafluorophosphate (LiPF6) was added to the above organic solvents to dissolve and mix thoroughly to obtain an electrolyte with a LiPF6 concentration of 1.15 mol / L.

[0074] Preparation of isolation membrane

[0075] A porous polyethylene film having a thickness of 16 μm was used as a separator.

[0076] Preparation of lithium-ion batteries

[0077] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, and then wound to obtain an electrode assembly. After the pole ear is welded, the electrode assembly is placed in an aluminum-plastic film, dried in a vacuum oven at 80°C for 12 hours to remove moisture, and then injected with the above-prepared electrolyte. After vacuum packaging, standing, formation (0.02C constant current charging to 3.5V, then 0.1C constant current charging to 3.9V), capacity, shaping and other processes, a lithium-ion battery is obtained. In this application, unless otherwise specified, it can be prepared by referring to conventional technical means in this field.

[0078] Test method:

[0079] (1) Test method for mass concentration

[0080] The lithium salt concentration C1 in the electrolyte was calculated by inductively coupled plasma (ICP) testing. A portion of the electrolyte was taken and weighed m1, which was dried in an oven at 120°C for 8 h. The mass of the remaining residual solid m2 was weighed. The mass concentration of the soluble polymer in the electrolyte m wt% = (m2-C1*m1) / m1.

[0081] (2) Thickness expansion rate test method

[0082] The expansion rate of the negative electrode plate is obtained by disassembling the battery cell and testing the anode plate; charging the fresh battery cell after formation to 3.91V, disassembling the corresponding battery cell to obtain the negative electrode plate, and using a micrometer to test the average thickness of the negative electrode plate to obtain the thickness T1; charging the cycled battery cell at 1C to the full charge voltage, and then charging at a constant voltage at the full charge voltage to a current of 0.05C, disassembling the corresponding battery cell, and using a micrometer to test the average thickness of the negative electrode plate to obtain the thickness T2; the expansion rate of the negative electrode plate is THK=T2-T1 / T1.

[0083] (3) Test method for high temperature cycle performance

[0084] At 45°C, charge the lithium-ion battery at a constant current of 1C to a full charge voltage of 4.5V, then charge it at a constant voltage of 0.05C at full charge voltage, and then discharge it at a constant current of 1C to 3.0V. This is a charge and discharge cycle, and record the discharge capacity of the first cycle of the lithium-ion battery. Cycle the lithium-ion battery 400 times according to the above method, and calculate the capacity retention rate of the 400th cycle. Among them, the capacity retention rate % = the discharge capacity of the current cycle / the discharge capacity of the first cycle.

[0085] (4) Test method for rate performance

[0086] At 25°C, the lithium-ion battery was charged at a constant current of 0.2C to the full charge voltage, then charged at the full charge voltage to a current of 0.02C, and then discharged at a constant current of 0.2C to 3.0V, and the discharge capacity at the 0.2C rate was recorded.

[0087] At 25°C, the lithium-ion battery was charged at a constant current of 0.5C to the full charge voltage, then charged at the full charge voltage to a current of 0.02C, and then discharged at a constant current of 2C to 3.0V, and the discharge capacity at the 2C rate was recorded.

[0088] 2C discharge capacity retention rate (%) = 2C rate discharge capacity / 0.2C rate discharge capacity × 100%.

[0089] Table 1

[0090]

[0091]

[0092] Combined with Table 1, by comparing Comparative Example 1 with Example 1-1, it can be seen that the silicon particles in Comparative Example 1 are not coated, and the thickness expansion rate of the negative electrode sheet containing silicon particles not coated with the surface coating layer is as high as 16.0%, and the discharge capacity retention rate at 2C is only 64.5%, while the silicon particles in Example 1-1 are coated with the surface coating layer. When the silicon-based material in Example 1-1 is used as the negative electrode active material to prepare a lithium ion battery, the thickness expansion rate of the negative electrode sheet is as low as 9.1%, which is significantly reduced by about 7% compared with the thickness expansion rate of Comparative Example 1, and its discharge capacity retention rate at 2C is as high as 79.3%, which is significantly improved by about 15% compared with the 2C discharge capacity retention rate of Comparative Example 1.

[0093] Compared with Example 1-1, Examples 1-2 and 1-3 selected other suitable alcohol-soluble resins as soluble polymers to prepare the surface coating layer to coat the silicon particles, and the prepared lithium-ion batteries had similar or better technical effects than Example 1-1. In particular, the alcohol-soluble resin used in Example 1-3 was polyurethane resin, and the thickness expansion rate of the negative electrode sheet in the lithium-ion battery prepared in Example 1-3 was only 8.2%, and its 2C discharge capacity retention rate was increased to 82%.

[0094] Compared with Example 1-3, Example 1-4, Example 1-5, and Example 1-6 further adjusted the mass ratio of the alcohol-soluble polymer to the silicon particles in Example 1-4, Example 1-5, and Example 1-6. It can be seen that when the ratio of the mass ratio decreases (the fraction of the alcohol-soluble polymer is small), the thickness of the surface coating layer decreases accordingly, resulting in the mass concentration of the alcohol-soluble polymer in the electrolyte being not within an appropriate range. The thickness expansion rate of the negative electrode plate in the prepared lithium-ion battery is significantly increased to 8.5%, and its 2C discharge capacity retention rate is reduced to 79.5%. Example 1-9 is similar, and when the ratio of the mass ratio increases (the fraction of the alcohol-soluble polymer is large), the thickness of the surface coating layer increases accordingly, which also results in the mass concentration of the alcohol-soluble polymer in the electrolyte being not within an appropriate range. Example 1-9 also has a similar conclusion.

[0095] Compared with Example 1-3, it can be seen that the surface coating layer contains an appropriate amount of single-walled carbon nanotubes, which can further improve the thickness expansion rate of the negative electrode sheet. Compared with Example 1-3, it can be seen that when the aspect ratio of the single-walled carbon nanotubes is adjusted to a suitable range, it is more conducive to reducing the thickness expansion rate of the negative electrode sheet and improving the rate performance of the lithium-ion battery.

[0096] Examples 2-1 to 2-11 in Table 2 are all adjusted based on Examples 1-11, see Table 2 for details.

[0097] Table 2

[0098]

[0099] It can be seen from Table 2 that the mass ratio of linear ester to cyclic ester in the electrolyte is in an appropriate range, which is conducive to improving the thickness expansion rate of the negative electrode sheet, and the porosity of the negative electrode sheet is appropriate, which can also better improve the problem of thickness rebound of the silicon system sheet during processing.

[0100] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate includes a negative electrode active material, the negative electrode active material includes a silicon-based material, and the silicon-based material is obtained by providing a surface coating layer on the surface of silicon particles; the surface coating layer includes a soluble polymer, and the soluble polymer is configured to be soluble in an electrolyte; The mass ratio of the soluble polymer to the silicon particles is (0.05-1.2):

1.

2. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the soluble polymer to the silicon particles is (0.3-0.5):

1.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: The surface coating layer also includes carbon nanotubes; The mass ratio of the carbon nanotubes to the silicon particles is (0.005-0.1):

1.

4. An electrochemical device, characterized in that The electrochemical device comprises a negative electrode plate; The negative electrode plate includes a negative electrode active material, the negative electrode active material includes a silicon-based material, and the silicon-based material is obtained by providing a surface coating layer on the surface of silicon particles; The surface coating layer includes a soluble polymer, and the soluble polymer is soluble in an electrolyte; After the electrochemical device is injected with the electrolyte, the mass concentration of the soluble polymer in the electrolyte is 0.2 wt % to 6 wt %.

5. The electrochemical device according to claim 4, characterized in that After the electrochemical device is injected with the electrolyte, the mass concentration of the soluble polymer in the electrolyte is 1.3 wt % to 1.5 wt %.

6. The electrochemical device according to claim 4, characterized in that The surface coating layer also includes carbon nanotubes; The electrochemical device satisfies at least one of the following conditions: (1) The mass ratio of the soluble polymer to the silicon particles is (0.05-1.2):1; (2) The mass ratio of the carbon nanotubes to the silicon particles is (0.005-0.1):1; (3) The carbon nanotubes include single-walled carbon nanotubes, and the aspect ratio of the single-walled carbon nanotubes is 1*10 4 Up to 4*10 4 .

7. The electrochemical device according to claim 6, characterized in that The electrochemical device satisfies at least one of the following conditions: (1) The mass ratio of the soluble polymer to the silicon particles is (0.3-0.5):1; (2) The mass ratio of the carbon nanotubes to the silicon particles is (0.01-0.05):1; (3) The carbon nanotubes include single-walled carbon nanotubes, and the aspect ratio of the single-walled carbon nanotubes is 2.5*10 4 Up to 3*10 4 .

8. The electrochemical device according to claim 4, characterized in that The soluble polymer includes an alcohol-soluble resin and satisfies at least one of the following conditions: (1) The molecular weight of the alcohol-soluble resin is 8*10 3 Up to 1.5*10 5 ; (2) The alcohol-soluble resin is selected from at least one of an alcohol-soluble polyamide resin, an alcohol-soluble acrylic resin or an alcohol-soluble polyurethane resin.

9. The electrochemical device according to claim 4, characterized in that The dissolution amount of the soluble polymer in the specific solution is greater than 80%; The specific solution includes a linear ester and a cyclic ester, and the mass ratio of the linear ester to the cyclic ester is 3:

1.

10. The electrochemical device according to claim 4, characterized in that At least one of the following conditions is met: (1) The porosity of the negative electrode sheet is 25% to 48%; (2) The electrolyte includes a linear ester and a cyclic ester, and the mass ratio of the linear ester to the cyclic ester is (1-4):(4-1).

11. The electrochemical device according to claim 4, characterized in that At least one of the following conditions is met: (1) The porosity of the negative electrode sheet is 25% to 33%; (2) The electrolyte comprises a linear ester and a cyclic ester, and the mass ratio of the linear ester to the cyclic ester is (1-3):

1.

12. The electrochemical device according to claim 4, characterized in that The thickness of the surface coating layer is 0.5 μm to 10 μm.

13. The electrochemical device according to claim 4, characterized in that The negative electrode active material also contains graphite, and the mass ratio of the silicon particles to the graphite is 1:23 to 29:

1.

14. An electronic device, characterized in that: The electronic device comprises the electrochemical device according to any one of claims 4 to 13.

Citation Information

Patent Citations

  • Resin for coating lithium-ion-battery active material, resin composition for coating lithium-ion-battery active material, and coated active material for lithium-ion battery

    CN105359309A

  • Silicon-based anode material for lithium ion battery and preparation method thereof

    CN110690433A

  • Silicon-based lithium ion battery negative electrode material and preparation method thereof

    CN110707316A

  • Silicon-based composite material for negative active material, negative plate and lithium ion battery

    CN112002883A

  • Negative electrode additive, secondary battery, battery module, battery pack and device

    CN112563463A

Cited By

  • Negative active material, negative pole piece comprising same, electrochemical device and electronic equipment

    CN121687902A